2022
DOI: 10.1007/s00432-022-04164-1
|View full text |Cite
|
Sign up to set email alerts
|

AURKA is a prognostic potential therapeutic target in skin cutaneous melanoma modulating the tumor microenvironment, apoptosis, and hypoxia

Abstract: Background: AURKA, Aurora kinase A encoding gene, is an important signaling hub gene for mitosis. In recent years, AURKA has been implicated in the occurrence and development of several cancers. However, its relationship with the tumor microenvironment in skin cutaneous melanoma (SKCM) and the molecular mechanisms underlying its effects are still unclear. Method:We adopted a variety of bioinformatics methods to comprehensively analyze the potential carcinogenesis of AURKA in SKCM, and constructed a prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…We next chose 12 malignancies to investigate the association between AURKA and immune cells in them, finding that all immune cells except Th2 cells were adversely connected with AURKA. Previous research ( Bustos-Moran et al, 2019 ; Sun et al, 2021 ; Long and Zhang, 2022 ) has shown that AURKA may impact T cells, reshape the immunosuppressive tumor microenvironment, apoptosis, and hypoxia and hence contribute to immunological control, particularly CD8 + T cells that govern Th1 regulation. For example, studies ( Han et al, 2020 ) suggest that decreasing Aurora-A activity or deleting the AURKA gene might boost IL10-induced infiltration and growth of CD8 + T cells in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…We next chose 12 malignancies to investigate the association between AURKA and immune cells in them, finding that all immune cells except Th2 cells were adversely connected with AURKA. Previous research ( Bustos-Moran et al, 2019 ; Sun et al, 2021 ; Long and Zhang, 2022 ) has shown that AURKA may impact T cells, reshape the immunosuppressive tumor microenvironment, apoptosis, and hypoxia and hence contribute to immunological control, particularly CD8 + T cells that govern Th1 regulation. For example, studies ( Han et al, 2020 ) suggest that decreasing Aurora-A activity or deleting the AURKA gene might boost IL10-induced infiltration and growth of CD8 + T cells in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cdk1 can also mediate phosphorylation of Ulk1 and Atg13, thus promoting autophagy 55 . Except Cdk1, other hub genes have not been studied in SCI, but they all have the functions of regulating cell cycle, promoting cell proliferation and inhibiting apoptosis, necroptosis, pyroptosis and ferroptosis in other diseases [57][58][59][60][61][62][63][64][65][66][67] .…”
Section: Discussionmentioning
confidence: 99%
“…In SKCM, the dysregulation of PCD pathways significantly contributes to multiple facets of tumorigenesis, encompassing tumor initiation, progression, and therapeutic responsiveness 11,12 . Apoptosis is particularly relevant in SKCM, since alterations in the expression of pro‐apoptotic and anti‐apoptotic proteins disrupt the delicate balance between cell survival and death, promoting tumor cell evasion of programmed death and facilitating tumor growth and metastasis 13,14 . Moreover, mounting evidence suggests the implication of alternative PCD mechanisms in SKCM, including pyroptosis and ferroptosis 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Apoptosis is particularly relevant in SKCM, since alterations in the expression of pro‐apoptotic and anti‐apoptotic proteins disrupt the delicate balance between cell survival and death, promoting tumor cell evasion of programmed death and facilitating tumor growth and metastasis. 13 , 14 Moreover, mounting evidence suggests the implication of alternative PCD mechanisms in SKCM, including pyroptosis and ferroptosis. 15 , 16 Pyroptosis has been implicated in promoting inflammation and fostering the progression of SKCM.…”
Section: Introductionmentioning
confidence: 99%